Assessing and improving needle exchange programs: gaps and problems in the literature - Ksobiech, Kate (BioMed Central, 2004)
Based on an extensive review of the needle exchange program (NEP) literature, the author sought to identify weaknesses in NEP evaluations published to date. Surprisingly, it was apparent that NEP researchers often fail to: (1) collect comparison/change data; (2) agree on appropriate and consistent dependent variables to measure; (3) use valid and reliable measurement instruments; (4) present clear operational definitions; (5) analyze outcome measures by gender/race/social context; (6) provide data on type of drug injected as it relates to risky drug and sexual behaviors; (7) measure HIV/AIDS knowledge; or, (8) clearly articulate desired NEP outcomes. Suggestions for future research are included, and conclusions about the overall state of NEP evaluative research are drawn.